Investigation on the behavior of rigid polyvinylchloride pipes subjected to uniaxial compression loads - Abdullah Ali Nasser Alhamati; Abdul Halim Ghazali; Jamalodin Norzaie (ASEAN Journal on Science and Technology for Development, 2006)
The objective of this research was to investigate the capability of rigid Polyvinylchloride (PVC-U) pipes to sustain axial loads. The behavior of PVC-U pipes specimens subjected to short-term uniaxial compression loads were experimentally investigated. Results of the load-displacement tests on pipes of different wall thickness, diameter, and specimen heights were recorded. The experimental test results show that the PVC-U pipes are capable of supporting loads greater than the required design load (3.4 kN). Increasing the pipe specimen height decreases the pipe strength for supporting the axial loads.  Euler buckling was observed in the pipe specimens with small diameter and long axial height. Furthermore, an attempt has been made to utilize the ANSYS finite element commercial package to model the pipe system using eight noded brick element and the results were compared with those obtained from the experimental tests. Good agreement was found between the two sets of results, within the elastic range of the load-displacement curve.